1995
DOI: 10.1074/jbc.270.49.29548
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Loops Regulates Transport Activity of Mitochondrial ADP/ATP Carrier Deduced from Formation of a Specific Intermolecular Disulfide Bridge Catalyzed by Copper-o-Phenanthroline

Abstract: The cross-linking reagent copper-o-phenanthroline complex (Cu(OP)2) specifically caused a decrease in the amount of the 30-kDa ADP/ATP carrier in bovine submitochondrial particles associated predominantly with formation of a 60-kDa protein consisting of a cross-linked dimer of the carrier. However, Cu(OP)2 had no effect on mitochondria. The transport of ADP via the carrier through submitochondrial particle membranes was found to be inhibited in parallel with the progress of intermolecular cross-linking. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 33 publications
9
116
1
Order By: Relevance
“…The proposed topology of the ANT, illustrated in Fig. 1, has been confirmed experimentally by specific labeling of the two ANT conformations with a range of membrane permeant and impermeant thiol and lysine reagents (see [6,13,[27][28][29][30][31]. Together with the use of photactivatable substrate analogues [32,33] these studies have also led to information on both the substrate binding sites and the conformational changes that occur during the translocation cycle.…”
Section: The Ant Exhibits Two Distinct Conformationsmentioning
confidence: 82%
See 1 more Smart Citation
“…The proposed topology of the ANT, illustrated in Fig. 1, has been confirmed experimentally by specific labeling of the two ANT conformations with a range of membrane permeant and impermeant thiol and lysine reagents (see [6,13,[27][28][29][30][31]. Together with the use of photactivatable substrate analogues [32,33] these studies have also led to information on both the substrate binding sites and the conformational changes that occur during the translocation cycle.…”
Section: The Ant Exhibits Two Distinct Conformationsmentioning
confidence: 82%
“…In support of this, a fusion protein of two tandem covalently linked yeast ANT molecules has been shown to be functional, with similar activity and inhibitor binding properties to the normal ANT [11,12]. Furthermore, the two subunits can be covalently cross-linked between the matrix facing Cys 56 residues of adjacent subunits using copper o-phenanthroline or bifunctional bimaleimides [13,14]. However, none of these observations rules out the possibility that a tetramer may be the minimal functional unit and some evidence for this has been presented [4].…”
Section: General Topological Featuresmentioning
confidence: 99%
“…Altogether, these data indicate that diamide-like thiol reactive agents oxidize and/or derivatize cysteine 56 of ANT. This cysteine residue faces the matrix side of ANT, between the ®rst two membrane-spanning transmembrane domains of ANT (Klingenberg, 1993;Majima et al, 1995;Palmieri, 1994). It thus constitutes a prime candidate for being identical with the oxidation-sensitive thiol of the PTPC that, based on its inaccessibility to a hydrophilic thiol crosslinker (monobromotrimethylammoniobimane), has been postulated to face the matrix side of the inner mitochondrial membrane (Costantini et al, 1995a(Costantini et al, , 1996(Costantini et al, , 1998.…”
Section: Resultsmentioning
confidence: 99%
“…ANT is a carrier protein that is able to form two conformational states, the c-state and the m-state. It has three reactive cysteines (Cys 56 , Cys 159 , and Cys 256 ) that are all located on putative matrix-facing loops and whose thiol groups selectively react with thiol reagents when in the m-state (8,9). Previous study showed that a derivative of atractyloside, carboxyatractyloside, fixes ANT in the c-state and greatly reduces the binding of ANT to phenylarsine oxide (PhAsO)-agarose, an affinity matrix that binds selectively with vicinal dithiols in proteins (15).…”
Section: Mt-21-induced Cytochrome C Release Is Enhanced By Mgmentioning
confidence: 99%
“…ANT has two conformational states, c-state and m-state, and ADP/ATP are transported via interconversion of these two states. In c-state a hydrophilic loop of the ANT, which is the nucleotide-binding site, faces toward cytoplasmic side of the inner membrane, and in m-state it is exposed to the matrix side (8,9). Bongkrekic acid inhibits PT pore opening and the release of cytochrome c via binding to ANT and fixing its conformation in the m-state (10,11).…”
mentioning
confidence: 99%